2015
DOI: 10.1146/annurev-cellbio-100814-125544
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Epigenetics

Abstract: Epigenetic mechanisms by which cells inherit information are, to a large extent, enabled by DNA methylation and posttranslational modifications of histone proteins. These modifications operate both to influence the structure of chromatin per se and to serve as recognition elements for proteins with motifs dedicated to binding particular modifications. Each of these modifications results from an enzyme that consumes one of several important metabolites during catalysis. Likewise, the removal of these marks ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
129
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(141 citation statements)
references
References 150 publications
(182 reference statements)
4
129
0
2
Order By: Relevance
“…Increasing evidence suggests that multiple pathways connect metabolism to chromatin regulation and epigenetic processes (8,9,20). In this study, our in silico screen revealed that multiple proteins with established roles in amino acid metabolism also have potential functions in chromatin.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Increasing evidence suggests that multiple pathways connect metabolism to chromatin regulation and epigenetic processes (8,9,20). In this study, our in silico screen revealed that multiple proteins with established roles in amino acid metabolism also have potential functions in chromatin.…”
Section: Discussionmentioning
confidence: 83%
“…A growing field in the study of chromatin is the intersection of epigenetic and chromatin dynamics with cellular metabolic processes (7)(8)(9). Although most metabolic proteins localize to the cytoplasm, a number of metabolic proteins are found in the nucleus, where they can regulate chromatin dynamics through at least two distinct mechanisms.…”
mentioning
confidence: 99%
“…Studies focusing on the developmental origin of health and disease have identified links between early nutrition and disease, consistent with the "developmental origins of health and disease" (DOHaD) hypothesis. This hypothesis postulates that early life development is critically sensitive to inadequate nutrition and other environmental factors, leading to permanent changes or marks in development that can influence the health of an individual in later life and increase their risk of disease [2,6,7,8].…”
Section: The Impact Of Haplotype-dependent Allele-specific Methylatiomentioning
confidence: 99%
“…The bioavailability of synthetic folic acid (monoglutamyl pteridine) is approximately 70% better than that of folate (mainly polyglutamyl pteridines) from dietary sources and thus the term dietary folate equivalent (DFE) is used to describe the effects of different folate molecular specie s (Joint FAO/WHO Expert Consultation on Human Vitamin and Mineral Requirements 1998). Folate prevents megaloblastic anemia (Chanarin 1987) and many other diseases because it is essential to the synthesis, repair (Lindahl 2013), and epigenetic regulation (Janke et al 2015) of DNA. Folate is therefore the link between diet, metabolism, and epigenetics (Janke et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Folate prevents megaloblastic anemia (Chanarin 1987) and many other diseases because it is essential to the synthesis, repair (Lindahl 2013), and epigenetic regulation (Janke et al 2015) of DNA. Folate is therefore the link between diet, metabolism, and epigenetics (Janke et al 2015). Thus, the mechanism by which folate prevents many diseases, such as neural tube defects (NTD), has been studied at the molecular level (Ichi et al 2012).…”
Section: Introductionmentioning
confidence: 99%